Energy metabolism in animals : Proceedings of the 15th symposium on energy metabolism in animals - Chwalibog, A.,; Jakobsen,K., (Biology - Book Archive 2000-2006., 2001)
At the 15th Symposium on Energy Metabolism in Animals, 10-16 September 2000 in Denmark, a wide variety of subjects came up for consideration covering both basic aspects and applied animal science. The symposium was organised around four main session themes:- I Methodology and techniques- II Environmental and dietary aspects- III Tissue and whole body metabolism- IV Growth, lactation and maintenance This time, different from before, the papers are dealing with all kind of animals, i.e. cattle, sheep, goat, pig and poultry, fish, ostrich, emu, mink, dog, cat, yak, rat, mice and man and not restricted to farm animals only. Professor Jens Christian Skou, Nobel Prize Winner showed up for the keynote lecture "The identification of the sodium-potassium pump, and its significance", an interesting contribution about the importance of the Na/K pump in animal physiology and energy metabolism. Results of a workshop on "Stable isotopes and indirect calorimetry" are reported as well as a "Glossary of terminology in animal and human energy metabolism". To focus the attention to new developments summaries of discussions per theme are included. The book provides a wide variety of readers in animal science and nutrition a lot of information to be used in research, teaching, extension service and animal production practice.